A framework to identify knowledge actor roles in enterprise social networks. Issue 4 (10th July 2017) - Hacker, Janine Viol; Bodendorf, Freimut; Lorenz, Pascal
Abstract : Purpose: Enterprise social networks (ESN) are increasingly used by companies to reinforce collaboration and knowledge sharing. While prior research has investigated ESN use practices, little is known about potential user roles emerging on these platforms. Against this backdrop, this paper develops an ESN knowledge actor role framework. Design/methodology/approach: The framework is constructed based on a systematic review of literature covering knowledge worker role typologies, user roles identified in public online social spaces as well as findings from ESN research. Findings: The ESN knowledge actor role framework distinguishes eight contributing and two reading roles. It describes the associated participation behaviours and establishes metrics to identify the roles. Research limitations/implications: Providing a notion of knowledge management-related roles in ESN, the framework enables a better understanding of knowledge processes and the involved actors. Moreover, the paper advances the field of ESN data analytics by designing a set of ESN metrics to characterise user behaviour. Practical implications: Understanding ESN user roles, in particular regarding their knowledge contributions to the platform, can improve knowledge transparency in companies. The framework may usefully support the identification and management of critical knowledge resources and support decision-making in the areas of human resources management and knowledge management. Originality/value: Providing a platform for knowledge-intensive interactions as well as record of user activities, ESN are well suited to observe and identify knowledge actor roles emerging in this context.